Influence of Seasonal and Monthly Variation on Blood Serum Total Protein in Ctenopharyngodon idella - Mansoori, Naseem Ahmad; Nichat, Avinash R. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
This study is serum protein of Ctenopharyngodon idella higher in breeding period. That value in post breeding slightly lower and pre–breathing less more than post breeding season in male. In female serum protein where higher in the post breeding. In the breeding season the serum protein is slightly lower and pre breeding value of serum protein less than breeding period. The mean values of female were higher in the post breathing period 5.65 gm% showing seasonal variation as 4.8 to 6.5 gm%. In the breeding season the mean value were very slightly lower side as were found in post breeding season, this period the mean value were 5.50±0.07gm% with seasonal variation of 4.4 to 6.9gm%. During summer pre breeding period the mean values 4.82±0.05 gm % with there seasonal variation of 4.0 to 5.7 gm%. In Male were higher breeding period as 5.65± 0.03 gm% showing seasonal variation as 4.5 to 6.3 gm %. In post breeding season the mean value was very slightly lower side as were found in breeding season in this period the mean value were 5.62±0.06 gm% with the seasonal variation of 4.5 to6.6gm%. During summer i.e. pre breeding period the mean value were 4.62±0.05gm% with their seasonal variation of 3.2 to5.6 gm%.